Effect of endodontic treatment on periodontal healing of grade 3 endo-periodontal lesions without root damage in periodontally compromised patients: a retrospective pilot study - Rütters, Maurice; Kim, Ti-Sun; Krisam, Johannes; El-Sayed, Shirin; Sayed, Nihad el (Clinical oral investigations, 2021)
There is little evidence about the effect of different treatment protocols for grade 3 endo-periodontal lesions without root damage in patients with periodontitis according to the new classification of periodontal disease. The aim of this study is to evaluate the impact of endodontic treatment on the achievement of periodontal healing.